The impact of information-developmental teaching of Science and Social Studies on student knowledge - Ljiljana G. Bujišić (Inovacije u Nastavi, 2025)
The comprehensive changes in the world, driven by the emergence of the latest digital technologies, also influence the need for changes in the field of education. The need for students to engage in research, collaboration, the environmental changes in students’ upbringing, the challenges of new spatial organization, and the presence of digital devices in everyday life have caused numerous recommendations for changes in the teaching process over the past decades. Despite potential resistance to accepting digital technology, the teacher’s role is to focus on developing both their own and students’ higher-order skills, such as applying information in similar situations, analysis, planning, and fostering critical thinking, among others. The use of Google Classroom in lessons offers students an opportunity to work differently, independently of space and time, encouraged by various interactive and free materials. During the COVID-19 virus pandemic, an experimental study was conducted with the fourth-grade students of primary schools, whereby the instrument was a test of knowledge. In our experimental research, students in the control group worked in the usual manner, while students in the experimental group used Google Classroom during Science and Social Studies lessons. The aim of the research was to determine whether and to what extent the integration of electronic learning in IT-developmental teaching of Science and Social Studies at a younger school age affects student knowledge in that field. After introducing the new method of work, the students in the experimental group demonstrated better knowledge in the given field, which indicates that information and communication technology has a positive impact on students’ knowledge acquisition. Implications for further research could focus on potential solutions for facilitating communication with students whose native language is not Serbian, as their numbers are increasing, as well as exploring the use of educational platforms for collaboration in working with students from vulnerable groups.